Intergranular Corrosion of Low Cr Ferritic Stainless Steel 429 Evaluated by the Optimized Double Loop Electrochemical Potentiokinetic Reactivation Test. (21st June 2015) - Li, Xiao-lei; Ni, Yi-fan; Jiang, Yi-ming; Li, Jin; Li, Li
Abstract : Intergranular corrosion (IGC) of Nb-Ti stabilized ferritic stainless steel (FSS) 429 was investigated using the double loop electrochemical potentiokinetic reactivation (DL-EPR) test combined with the microstructure observation. The results indicated that the optimized DL-EPR test condition for FSS 429 was the solution of 0.5 M H2 SO4 + 0.0001 M KSCN with a scanning rate of 100 mV/min at 30°C. Based on this condition, the specimens aging at 400–700°C for different duration were tested and a time-temperature-sensitization (TTS) curve for FSS 429 was obtained, which reveals the sensitization nose was located around 550°C. The critical I r / I a value was determined to be about 3% above which IGC occurred. After aging treatment, Cr depletion zone was detected using energy dispersive spectroscopy (EDS), most possibly due to Cr segregation around intergranular TiC and NbC.